Mire veja : travessias epifânicas nas veredas do Grande Sertão - Teles, Daniele Cristina Agostinho (2012)
The objective of this research is to offer a critical view of the novel Grande Sertão: Veredas (1956), by João Guimarães Rosa, in the light of the epiphany concept developed by the Irish writer James Joyce, that means, to apart it from its original place the religion moving it to the literary field as one of its aesthetic procedures. Based on the bibliographical survey of the critical fortune focused on the titles evidencing some thematic proximity as, for example, the construction of Rosa s language in what concerns lexical innovation and hard work with the language and the links with metaphysics and alchemy, the problematic of the research is concentrated on the speculation on the presence of epiphanic procedures in the novel s writing, its closeness and distance to Joyce s concept, as well as the links established with the aesthetical effect. The hypothesis we raised is that the singularity of the epiphanic writing process in GSV lies in the friction created by Rosa s text between writing and talking, the text and the work according to Paul Zumthor s concepts, in short, between what the writing suggests and what the reader reads-hears-sees-embodies-interprets. Furthermore, it is in Riobaldo s narrative act that the new sight of the lived matter occurs, which reverberates in the writing sphere in the relation between the authorial creative process and the effect on the reception. The methodology of the analysis favors the enunciative scenes which generate the great transformations in the narrator s trajectory - which are Diadorim, the Siruiz song and the pact with the devil following the assumption that GSV s epiphanic process resides in the intercross of two enunciative scenes: the one that is built on the oral level (from the narrator Riobaldo to the interlocutor) and the other one which is constructed between the subject of the writing the author creator João Guimarães Rosa Riobaldo s partner, with whom he shares the authorship between voice, talking and writing, the novel itself and the other to whom it is destined, which, now, is the reader. The results demonstrate that the epiphany, besides its character of apparition, revelation and manifestation, acts as GSV s aesthetical and compositional procedure, and manifests itself in the microphysics of its poetical language, in Riobaldo s oral narrative as well as in the authorial writing